PENGGUNAAN TEKNOLOGI WEB UNTUK SISTEM E-LEARNING ADAPTIF DI PENDIDIKAN – SYSTEMATIC LITERATURE REVIEW - Listi Aulia; Yugistira Yugistira; Khusnul Khatimah; Andi Nurfadillah; Erwin Erwin; Dayanti Dayanti (Plexi Digital Indonesia, 2026)
The rapid development of web technology has significantly transformed the education sector, particularly in the implementation of adaptive e-learning systems. Adaptive e-learning utilizes learner data to personalize learning content, learning paths, and feedback according to individual needs and abilities. This study aims to analyze research trends, technologies, and findings related to the use of web technology in adaptive e-learning systems through a Systematic Literature Review (SLR). The review was conducted on 20 selected scientific articles published between 2020 and 2025 obtained from reputable digital databases. The results show that web-based adaptive e-learning systems contribute positively to learning effectiveness, student engagement, and learning efficiency. Key technologies identified include learning analytics, artificial intelligence, machine learning, and web-based learning management systems. Despite the benefits, challenges remain in terms of system complexity, data privacy, infrastructure readiness, and educator competence. This study provides a comprehensive overview of the current state of research and offers insights for future development of adaptive e-learning systems in education.